Description of peptide bond planarity from high-resolution neutron crystallography - Yuya Hanazono; Yu Hirano; Taro Tamada; Kunio Miki (Biophysics and Physicobiology, 2023)
Neutron crystallography is a highly effective method for visualizing hydrogen atoms in proteins. In our recent study, we successfully determined the high-resolution (1.2 Å) neutron structure of high-potential iron-sulfur protein, refining the coordinates of some amide protons without any geometric restraints. Interestingly, we observed that amide protons are deviated from the peptide plane due to electrostatic interactions. Moreover, the difference in the position of the amide proton of Cys75 between reduced and oxidized states is possibly attributed to the electron storage capacity of the iron-sulfur cluster. Additionally, we have discussed about the rigidity of the iron-sulfur cluster based on the results of the hydrogen-deuterium exchange. Our research underscores the significance of neutron crystallography in protein structure elucidation, enriching our understanding of protein functions at an atomic resolution.